Characterization of a novel calcium response element in the glucagon gene - Fürstenau, Ursel; Schwaninger, Markus; Blume, Roland; Jendrusch, Eva-Maria; Knepel, Willhart (The journal of biological chemistry, 1999)
To maintain blood glucose levels within narrow limits, the synthesis and secretion of pancreatic islet hormones is controlled by a variety of extracellular signals. Depolarization-induced calcium influx into islet cells has been shown to stimulate glucagon gene transcription through the transcription factor cAMP response element-binding protein that binds to the glucagon cAMP response element. By transient transfection of glucagon-reporter fusion genes into islet cell lines, this study identified a second calcium response element in the glucagon gene (G2 element, from −165 to −200). Membrane depolarization was found to induce the binding of a nuclear complex with NFATp-like immunoreactivity to the G2 element. Consistent with nuclear translocation, a comigrating complex was found in cytosolic extracts of unstimulated cells, and the induction of nuclear protein binding was blocked by inhibition of calcineurin phosphatase activity by FK506. A mutational analysis of G2 function and nuclear protein binding as well as the effect of FK506 indicate that calcium responsiveness is conferred to the G2 element by NFATp functionally interacting with HNF-3β binding to a closely associated site. Transcription factors of the NFAT family are known to cooperate with AP-1 proteins in T cells for calcium-dependent activation of cytokine genes. This study shows a novel pairing of NFATp with the cell lineage-specific transcription factor HNF-3β in islet cells to form a novel calcium response element in the glucagon gene.
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 01.04.2021